THE EFFECT OF WORK ATTITUDE, EMPLOYEE LOYALTY, WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN KPP PRATAMA MEDAN EAST - Dewi Suma; Budi Alamsyah Siregar (SEAN Institute, 2023)
The purpose of this study is to ascertain how employee performance at KPP Pratama Medan Timur is impacted by work attitude, employee loyalty, and work discipline. Because the data acquired will be realized in the form of numbers and evaluated using statistics, the methodology employed in this study is a quantitative methodology. The effectiveness of training, competency, and employee loyalty on employee productivity at KPP Pratama Medan is assessed using this methodology. 86 KPP Pratama Medan employees made up the study's sample population. In the absence of a mixed variable of workplace attitudes regarding employee performance, 435 implies that it is equivalent to 2.427. Work attitude, work loyalty, and work discipline all have a favorable impact on employees' performance. Accordingly, any improvement in work attitude, organizational climate, and training variables will have a beneficial impact on employee performance. Loyalty is 0.427 and work discipline is 0.195.